Research on the Evaluation Algorithm of Social Capital Influence of Enterprise Network Marketing - Yu Yu (Hindawi-Wiley, 2021)
In order to improve the problems of low recognition of evaluation results of traditional methods, comprehensive evaluation results, low accuracy, and small number of marketing advertisements, this paper proposes a social capital impact evaluation algorithm for corporate network marketing. It analyzes the influence dimension of social capital from the three dimensions of structure, relationship, and cognition. Starting from different dimensions, by constructing an evaluation index system, calculating evaluation index weights, and designing evaluation algorithms, a complete evaluation index is obtained. Finally, the impact evaluation algorithm is designed using the analytic hierarchy process. The results show that the evaluation results of the algorithm have a high degree of recognition, the evaluation results are comprehensive and accurate, and the amount of marketing advertisements is high, indicating that the algorithm has a high application value.